2016
DOI: 10.1111/jph.12521
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma aureoviride URM 5158 and Trichoderma hamatum URM 6656 are Biocontrol Agents that act against Cassava Root rot through different Mechanisms

Abstract: Trichoderma has been used to manage a large number of pathogens, but there is a gap in the mechanisms used by these biocontrol agents regarding the physiological response of cassava plants (Manihot esculenta) when it is subjected to cassava root rot. The aims of this study were to investigate the antagonist activity of ten Trichoderma isolates against Fusarium solani on potato dextrose Agar (PDA), to quantify the chitinase production, to select and test in vivo the best isolate from each experiment and to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
(68 reference statements)
1
16
0
1
Order By: Relevance
“…This finding suggests that mechanisms other than the production of secondary metabolites account for the remaining 50% of the antifungal activity observed by living endophytes. We speculate that this could be related to the presence of alternative biocontrol strategies such as the production of chitinases for example that are known to inhibit the growth of fungal phytopathogens ( Da Silva et al, 2016 ). However, more detailed research work is required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that mechanisms other than the production of secondary metabolites account for the remaining 50% of the antifungal activity observed by living endophytes. We speculate that this could be related to the presence of alternative biocontrol strategies such as the production of chitinases for example that are known to inhibit the growth of fungal phytopathogens ( Da Silva et al, 2016 ). However, more detailed research work is required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sacc. and Scytalidium lignicola Pesante (SILVA et al, 2016). The bacterial isolate selected was Pseudomonas UAGF 14 from the collection of microbial cultures of the Microbial Genetics and Biotechnology Laboratory of the Universidade Federal Rural de Pernambuco -UFRPE.…”
Section: Obtaining the Isolates And Preparing The Inoculummentioning
confidence: 99%
“…These microorganisms may also influence the availability of micronutrients by solubilization, chelation and soil reactions (ADAK et al, 2016). Fungus of the Trichoderma genus has been studied by producing a series of extracellular enzymes (HARMAN et al, 2004), such as chitinases, lipases, proteases and glucanases, capable of degrading fungal cell walls (SILVA et al, 2016). These enzymes also act in the decomposition of plant residues as well as in the inhibition of pathogens, interfering with the development of plants (SHANMUGAIAH et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the enzymes β-1,3-glucanase and protease were produced when T. harzianum mycelia were transferred from a medium containing glucose as the sole carbon source to medium containing cell walls of Botrytis cinerea [12]. Silva et al [13] reported that 10 different chitinase producing Trichoderma strains varied in their enzyme activity, with higher chitinase activity resulting in a stronger inhibitory effect towards the pathogen.…”
Section: Introductionmentioning
confidence: 99%